Pengaruh Knalpot Standar Dan Knalpot Standar Modifikasi Terhadap Daya Dan Torsi Sepeda Motor 2 Tak - Feriansah, Arif; Prabowo, Eko (Surya Teknika : Jurnal Ilmiah Teknik Mesin, 2021)
Technological developments that continue to develop today are increasingly making it easier for humans to do their jobs, as well as what is happening in the automotive world with the existence of these new technologies, it will make it easier for mechanics to do their jobs because of demands from consumers or desires and the mechanics themselves are constantly evolving. Knowing the effect of standard exhaust and modifications to the power and torque of the RX king 135cc motorcycle. This test was carried out using a dynotest tool, the influence of a standard exhaust and a modified exhaust of 2mm, 4mm, 6mm, and 8mm filter holes. produces the most optimal increase in power in the variation of the 2mm exhaust filter with a result of 16.6hp at 9059 rpm engine speed. As for the optimal torque performance, the standard exhaust produces a maximum torque of 14.43 Nm at 6289 rpm engine speed.Keywords: Exhaust, Power and Torque.